Validation of Messenger Ribonucleic Acid Markers Differentiating Among Human Acute Respiratory Distress Syndrome Subgroups in an Ovine Model of Acute Respiratory Distress Syndrome Phenotypes - Wildi, Karin; Hyslop, Kieran; Millar, Jonathan; Livingstone, Samantha; Passmore, Margaret R.; Bouquet, Mahé; Wilson, Emily; LiBassi, Gianluigi; Fraser, John F.; Suen, Jacky Y. (Frontiers in Medicine, 2022)
The discovery of biological subphenotypes in ARDS offers a new approach to ARDS in general and possibly targeted treatment, but little is known about the underlying biology yet. To validate our recently described ovine ARDS phenotypes model, we compared a subset of messenger ribonucleic acid (mRNA) markers in leukocytes as reported before to display differential expression between human ARDS subphenotypes to the expression in lung tissue in our ovine ARDS phenotypes model. We studied 23 anesthetized sheep on mechanical ventilation with observation times between 6 and 24 hours. They were randomly allocated to the two phenotypes (n=14 to Ph1 (hypoinflammatory) and n=9 to Ph2 (hyperinflammatory)). At study end, lung tissue was harvested and preserved in RNAlater. After tissue homogenization in TRIzol, total RNA was extracted and custom capture and reporter probes designed by NanoString Technologies were used to measure the expression of 14 genes of interest and the 6 housekeeping genes on a nCounter SPRINT profiler. Among the 14 mRNA markers, in all animals over all time points, 13 markers showed the same trend in ovine Ph2/Ph1 as previously reported in humans: MMP8, OLFM4, RETN, GPR84, LCN2, ANKRD22, CD177, TNC1 expression was higher in Ph2 and MME, ADGRE3, TGFBI, HAL and SULF2 expression was higher in Ph1. These expression patterns could be found when different sources of mRNA – blood leucocytes and lung tissue – were compared. In human and ovine ARDS subgroups, similar activated pathways might be involved (e.g. oxidative phosphorylation, NF-κB pathway) that result in specific phenotypes.